1978
DOI: 10.1086/336985
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes During the Germination of Cattleya aurantiaca (Orchidaceae)

Abstract: Se~s of Cattleya 011ra11t~aca grown ~ymbiotically on a medium containing sucrose as the sole source of organic carbon developed into leaf-bearing plants. Those sown on the same medium without sugar reached the protocorm stage but did not differentiate further. Cross transfers of seedlings between the two media indicated that following 21-30 days of growth on the sucrose-containing medium subsequent development may_proceed in the absence of sugar. Levels of chlorophyll and ribulose-1,5-diphosphate carboxylase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…These results suggest that a physiological change takes place in the mycorrhiza which stops movement of carbon from fungus to plant. The developmental stage at which this change takes place appears from our work to be much later than the development of the first leaf as suggested by Harrison & Arditti (1978) for a Cattleya sp. Although this change does not appear to be readily reversible (e.g.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…These results suggest that a physiological change takes place in the mycorrhiza which stops movement of carbon from fungus to plant. The developmental stage at which this change takes place appears from our work to be much later than the development of the first leaf as suggested by Harrison & Arditti (1978) for a Cattleya sp. Although this change does not appear to be readily reversible (e.g.…”
Section: Discussionsupporting
confidence: 44%
“…It is not known whether mature photosynthetic orchids derive carbon via their endophyte. Harrison & Arditti (1978) found that uninfected seedlings of a Cattleya sp. were dependent on a source of external carbohydrate until they were about seven weeks old, when the appearance of the first leaf led to independence and autotrophic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The pathway of carbon in very young protocorms of succulent orchids could well be a Cg photosynthesis. Harrison and Arditti (1978) recently measured the RUDP carboxylase activity in germinating Cattleya seedlings. The level of activity correlated well with the ability of the young seedling to photosynthesize.…”
Section: Discussionmentioning
confidence: 99%
“…If the Cycnoches seeds contain as much lipid energy as fresh coconut solid endosperm (1470 kJ 100 g −1 ), the total is still a minuscule 212 kJ 14.4 g −1 or 0.000419618 kJ seed −1 . This assumption can be made because orchid seeds, like coconuts, are fatty in nature (Harrison, 1977; Harrison and Arditti, 1978; Arditti and Ernst, 1984) and may contain as much as 32% lipids (Knudson, 1929; Arditti, 1967, 1979, 1992) vs. 34% for coconuts.…”
Section: Seedmentioning
confidence: 99%
“…Their seeds are small and balloon‐like (for reviews, see Arditti and Abdul Ghani, 2000; Yam et al, 2002a) and contain only limited food reserves (for reviews, see Arditti, 1992; Yam et al, 2002b). However, the seeds are also not equipped with the metabolic machinery required for the utilization of the starch and lipids they do contain (Harrison, 1977; Harrison and Arditti, 1978). During the early stages of germination they depend on fungi for nutrients.…”
Section: Seedmentioning
confidence: 99%